2009
DOI: 10.1111/j.1524-475x.2009.00540.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism leading to the development of pressure ulcers based on shear force and pressures during a bed operation: Influence of body types, body positions, and knee positions

Abstract: Surface pressures and shear forces were measured in order to clarify the mechanism leading to the development of a pressure ulcer at five sites on the body during the operation of a bed (bed) using a device for simultaneously measuring pressure and shear force. Changes of shear force and pressure when three body types adopted different supine positions, with or without raising/bending the knees (raising the knees), were investigated and analyzed. The results are as follows: a slender body type tends to have th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 9 publications
0
34
0
Order By: Relevance
“…Schubert's work (Schubert and Fagrell, 1989) concluded that significantly more pressure sores over the sacrum area than over the gluteus region is due to the comparatively poorer regulation of microvascular flow in the area. The blood flow cessation in compressed areas is caused by a widespread arterial-arteriolar collapse in diastole; as the volume of blood injected during the systolic peak is too small to expand into the distal sections of the precapillary vessels (Nielsen, 1983;Holstein et al, 1979;Holloway et al, 1976;Mimura et al, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Schubert's work (Schubert and Fagrell, 1989) concluded that significantly more pressure sores over the sacrum area than over the gluteus region is due to the comparatively poorer regulation of microvascular flow in the area. The blood flow cessation in compressed areas is caused by a widespread arterial-arteriolar collapse in diastole; as the volume of blood injected during the systolic peak is too small to expand into the distal sections of the precapillary vessels (Nielsen, 1983;Holstein et al, 1979;Holloway et al, 1976;Mimura et al, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…A higher angle of head elevation has been reported to induce PUs in lower sacral region. 17,34 In particular Sanada and coinvestigators 17 reported that 77.8% of 155 PUs on the upper part of sacral region occurred despite lower elevation of head (Ͻ30Њ). In contrast, PUs on the lower sacral region and coccyx tended to occur with higher elevation of the head (Ͼ30Њ or while sitting).…”
Section: Leaf Pumentioning
confidence: 99%
“…Other researchers have reported that shear forces in the sacral region are influenced by the angle of elevation of the head and shoulders. 33,34 This shear force might be reduced by creating a gap between the patient's back and the bed surface at the time of the elevation. However, nurses in our study did not attempt this maneuver in patients who developed leaf PU and further research is needed to evaluate the effect of this type of positioning.…”
Section: Leaf Pumentioning
confidence: 99%
“…In a more recent study, Mimura et al 10 evaluated backrest elevation, body type, knee elevation, and position in the bed. Pressure was evaluated using sensor plates in 14 healthy volunteers (slender, average, and obese), continually in 5 sites (sacrum, lateral sacrum, coccyx, scapula, and posterior thigh) during constant backrest elevations from 0 to 80 degrees.…”
Section: Pressure Ulcersmentioning
confidence: 99%
“…9 Higher backrest elevation increases tissue pressure and shear, which facilitates pressure ulcer formation. 10 To limit this effect, in the sacral area especially, guidelines limit the backrest elevation to the lowest degree of elevation consistent with medical conditions 11 or to 30 degrees for an individual on bedrest 12,13 (Table 1). …”
mentioning
confidence: 99%